Ressocialização: a comunicação como caminho epistêmico de reconstrução do sistema prisional - Silva, Breno Inácio da (Universidade do Vale do Rio dos Sinos, 2021)
This research sought to understand the intricacies of the constitution of collective imaginaries about crime, criminal, punishment and resocialization, starting from the affectations of the communicational structure. It was a work built on an interface between the fields of Communication and Law, so that the set of strategies, grammars, regulations and processes that somehow intersect by interactional devices and engender specific articulations between the actors involved were observed. It contributed to the theoretical aspect of both the Communicational and Legal contexts, which were necessarily crossed by philosophy, anthropology, sociology and by the amateur's daily work. From the communicational field, concepts such as mediatization, circulation, interactional and imaginary devices were used more strongly, while from the legal field formal concepts of crime, criminal, punishment and resocialization emerged, as well as normative elements, in order to tension them, causing systemic irritation between these fields. This tensioning process included the observation of the amateurs’ action, those who, in particular, through social networks, daily express themselves on the topic, exposing their perceptions and affections. From the collected materialities, it was possible to observe that the process of circulation of concepts, meanings, and values related to the investigated elements is being reconstructed all the time, generating other meanings that directly impact the constitution of the collective imaginary, especially on the notion of resocialization. In the methodological field – given the particularities of the research proposed and its dynamic and daily transformation – it was necessary to observe how the methods, chosen a priori, offered indications of the need for other methodological attempts. With the materials collected during the research, it became possible to infer that the defeat of the prison system, with regard to the justification of its existence, resocializing, having even been declared by the Brazilian Supreme Court to have an unconstitutional state of things, is due to extremely marked and seriously dangerous for the constructions of communicational nature, and less for the juridical elements themselves. In this context, the naturalized use of discursive strategies of deletion, invisibility, and depersonalization of subjects was observed. Thus, a possible epistemic construct was glimpsed in the communication field that can, without a doubt, change the course of prison reality and its statistics, at least until it is definitively understood that the punishment by the violence of punishment alone is just absolutely ineffective. The human being will always be greater than his mistake.
Keywords: Circulação; Midiatização; Imaginário; Criminoso; Ressocialização; Circulation; Mediatization; Device; Imaginary; Criminal; Resocialization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação